Co2 methanation over ni/al@mal2O4 (M = Zn, Mg, or Mn) catalysts - Le, Thien An; Kim, Jieun; Jeong, Yu Ri; Park, Eun Duck (Catalysts, 2019)
In this study, unique core-shell aluminate spinel supports, Al@MAl2O4 (M = Zn, Mg, or Mn), were obtained by simple hydrothermal surface oxidation and were applied to the preparation of supported Ni catalysts for CO2 methanation. For comparison, CO methanation was also evaluated using the same catalysts. The prepared catalysts were characterized with a variety of techniques, including N2 physisorption, CO2 chemisorption, H2 chemisorption, temperature-programmed reduction with H2, temperature-programmed desorption of CO2, X-ray diffraction, high-resolution transmission electron microscopy, and in-situ diffuse reflectance infrared Fourier transform spectroscopy. The combination of supports with core-shell spinel structures and Ni doping with a deposition–precipitation method created outstanding catalytic performance of the Ni catalysts supported on Al@MgAl2O4 and Al@MnAl2O4 due to improved dispersion of Ni nanoparticles and creation of moderate basic sites with suitable strength. Good stability of Ni/Al@MnAl2O4 catalyst was also confirmed in the study.
Keywords: Al@MAl2O4; CO methanation; CO2 methanation; Core-shell; Deposition-precipitation; Ni catalyst; Ni/Al@MAl2O4